2016
DOI: 10.1038/srep39463
|View full text |Cite
|
Sign up to set email alerts
|

Use of PEG-asparaginase in newly diagnosed adults with standard-risk acute lymphoblastic leukemia compared with E. coli-asparaginase: a retrospective single-center study

Abstract: Acute lymphoblastic leukemia (ALL) is a heterogeneous disease, and the long-term survival varies with different ages. We performed a retrospective analysis of 122 newly diagnosed adults with standard-risk ALL treated with Escherichia coli asparaginase (E. coli-asparaginase, n = 50) and polyethylene glycol-conjugated asparaginase (PEG-asparaginase, n = 72). No treatment-related mortality (TRM) occurred in the E. coli-asparaginase group, and 3 TRM events occurred in the PEG-asparaginase group without relation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 53 publications
2
5
0
4
Order By: Relevance
“…Hepatotoxicity was The occurrence of liver toxicity during remission induction determines subsequent on-time delivery of chemotherapy. In fact, chemotherapy was discontinued or delayed in 7 patients in our study and this agrees with other reports [4,6]. However, it should be noted that most PEG-ASP toxic effects are manageable and reversible.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Hepatotoxicity was The occurrence of liver toxicity during remission induction determines subsequent on-time delivery of chemotherapy. In fact, chemotherapy was discontinued or delayed in 7 patients in our study and this agrees with other reports [4,6]. However, it should be noted that most PEG-ASP toxic effects are manageable and reversible.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to above-mentioned studies, only single patients developed grade 3/4 PEG-ASP-related toxicities in an analysis reported by Douer et al; where hyperbilirubinemia and transaminitis were found in 8% and 12% of patients, respectively. Although decreased fibrinogen and antithrombin concentrations were not associated with bleeding events, cryoprecipitate was prophylactically administered [6]. This supports our findings that no bleeding events were observed in our patient population despite severe hyperfibrinogenemia and decreased AT level after PEG-ASP in some tested patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“… 3 Asparaginase is an important component of chemotherapeutic regimens for acute lymphoblastic leukemia (ALL). 4 , 5 In addition, asparaginase exhibits antitumor activity against NK cell tumors in vitro and in vivo. 6 , 7 In 2000, Yong et al 8 conducted the first effective clinical trial of asparaginase in refractory or relapsed ENKTL.…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 In 2000, Yong et al 8 conducted the first effective clinical trial of asparaginase in refractory or relapsed ENKTL. Since then, various asparaginase-based regimens 4 , 5 have emerged as promising treatments for ENKTL. However, a number of patients are resistant to asparaginase, leading to treatment failure and poor prognosis.…”
Section: Introductionmentioning
confidence: 99%